2001
DOI: 10.1097/00003246-200108000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Relative roles of vascular and airspace pressures in ventilator-induced lung injury

Abstract: Isolated phasic elevations of pulmonary artery pressure may cause less damage than those occurring during intermittent positive pressure mechanical ventilation, suggesting that cyclic changes in perivascular pressure surrounding extra-alveolar vessels may be important in the genesis of ventilator-induced lung injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 25 publications
1
37
1
2
Order By: Relevance
“…Increased transmural pulmonary vascular pressure in the context of an increased vascular permeability greatly increases the risk of pulmonary edema through vascular leakage (16). Increases in pulmonary transmural vascular pressures have also been shown to worsen VILI (17). During inspiratory efforts intrathoracic pressure becomes negative and the intrathoracic blood volume increases.…”
Section: Spontaneous Breathing During Mechanical Ventilationmentioning
confidence: 99%
“…Increased transmural pulmonary vascular pressure in the context of an increased vascular permeability greatly increases the risk of pulmonary edema through vascular leakage (16). Increases in pulmonary transmural vascular pressures have also been shown to worsen VILI (17). During inspiratory efforts intrathoracic pressure becomes negative and the intrathoracic blood volume increases.…”
Section: Spontaneous Breathing During Mechanical Ventilationmentioning
confidence: 99%
“…These data refer to the magnitude of strain (a rough equivalent of end-inspiratory lung volume). However, it has been shown, both in vitro and in vivo, that the duration of strain, as well as its amplitude and frequency, may increase the injury [39][40][41][42]. Interestingly, for the same magnitude of strain, reducing its table 1).…”
Section: Alveolar Cellsmentioning
confidence: 99%
“…First, high capillary pressure may induce stress failure with increased permeability [53] and any increase in pressure increases oedema formation [57]. Moreover, it has been shown that cyclic changes in perivascular pressure surrounding extra-alveolar vessels due to mechanical ventilation cause greater oedema than isolated phasic elevation of pulmonary artery pressure without mechanical ventilation [41]. Finally, not only elevated but also low capillary pressure may damage the lung.…”
Section: Lung Capillariesmentioning
confidence: 99%
“…Recent clinical trials in patients with ALI or ARDS have demonstrated that lung-protective strategies led to improvements in clinical outcomes [3,5]. Vascular pressures and flow can also play a role in oedema formation, and it has been shown that lung injury can be significantly decreased in a fixed mechanical ventilation model, if pulmonary vascular pressures are strictly limited [6,7].…”
mentioning
confidence: 99%
“…Mechanisms explaining lung damage include: tangential shearing forces that produce stress on the alveoli wall, sustain epithelial and endothelial damage in such a way that capillary stress fractures and eventually haemorrhagic oedema may occur [6,13].…”
mentioning
confidence: 99%